2020
DOI: 10.1590/1984-0462/2020/38/2019027
|View full text |Cite
|
Sign up to set email alerts
|

Charcterization of Feeding of Children Under 24 Months in Units Cared by the Family Health Strategy

Abstract: Objective: To describe the median age of introduction and regular food intake by young children in units of the Family Health Strategy. Methods: Cross-sectional study with 283 young children chosen by uniform stratified cluster sampling. Socio-demographic data on the mother and the child’s food intake were collected (age of food introduction and weekly frequency). Foods were grouped into in natura/minimally processed (G1); culinary ingredients (G2); processed (G3) and ultra-processed (G4). The survival anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“… 1 On the other hand, another study in the same State showed that exclusive breast feeding until the age of 6 months occurred only among 24.9% of the participants, and that only 49% of the mothers participated in groups about breast feeding. 2 Such data, found in different studies, agree that weaning is, in fact, early among Brazilian families.…”
mentioning
confidence: 65%
“… 1 On the other hand, another study in the same State showed that exclusive breast feeding until the age of 6 months occurred only among 24.9% of the participants, and that only 49% of the mothers participated in groups about breast feeding. 2 Such data, found in different studies, agree that weaning is, in fact, early among Brazilian families.…”
mentioning
confidence: 65%